“Voi, gentiluomini, siete gli storici”. Mary Astell e la “lunga” Rivoluzione inglese - Cappuccilli, Eleonora (Studi Politici, 2023)
In the long English Revolution of the seventeenth century, Mary Astell (1666-1731) gave one of the most original contributions to the debate accompanying the birth of the modern state. Drawing on the historical experience of English women such as petitioners, pamphleteers, prophetesses, dissenters as well as queens and literary women, who made forays into the rising public sphere, Astell conveys a critique of patriarchal relationships formalized in the English law and expressed in the reflection of both Filmer and social contract theorists. At the same time she asserted the necessary union of Anglican Church and absolute monarchy to ensure peace and order. This article investigates the unstable relationship between theology, politics and the critique of patriarchy in Astell’s thought as a contradictory elaboration of women’s contribution to early modern constitutional transformations in England.